Hubungan Ketakutan akan Hipoglikemia dengan Manajemen Diri Pasien Diabetes Melitus Tipe 2 di RSD dr. Soebandi Jember - Novian Dwi Roessanti; Jon Hafan Sutawardana; Kushariyadi Kushariyadi (Pustaka Kesehatan, 2022)
Hypoglycemia is a complication of diabetes that causes unpleasant symptoms and fear for recurrence. This fear can influence diabetes management and patient metabolic control. The study aimed to analyze the relationship between fear of hypoglycemia and self-management of type 2 DM patients at dr. Soebandi Jember general hospital. The fear of hypoglycemia variable was measured using the Fear of Hypoglycemia Scale questionnaire (FH-15) and the variable of diabetes self-management was measured by the Diabetes Self-Management Questionnaire (DSMQ). The sample was 84 respondents that recruited using consecutive sampling method. Data was analyzed using the Spearman correlation test with α = 0.05. The results showed that patients did not experience fear of hypoglycemia (78.6%) and self-management of diabetic patients showed a good category (77.4%). There is a significant and positive correlation between the two variables (p-value = 0.012 and r = 0.272) which means that the more fearful the patient the more self-management gets worse, and conversely the less afraid of the patient the better self-management of diabetes. Family involvement is support for patients in controlling their fears, recognizing signs of hypoglycemia and as a reminder in managing proper diabetes. Diet control is an indicator of diabetes management that must be considered for patients to improve their health status by optimizing nutrition to prevent recurrent hypoglycemia.